Efeito de promotores tumorais em pele de gerbil, Meriones unguiculatus - Guzmán-Silva, Maria Angélica (2022)
In order to explaín the biological basis of the adult gerbil skin relative resistance to chemical carcinogenesis it was characterized the effect of cróton oil and benzoyl peroxide tumor promoters by studying the morphologicàl changès related to promotion and induced in adult gerbil skin accordingto dífferent doses, treatment frequencies, and associated pretreatment with the tumor initiator methylcholanthrene, through biphasic and triphasic carcinogenesis protocols. Similar degree of hyperkeratosis and dose-dependent hyperplasia were induced in the interfollicular epidermis after one topical application of croton oll (0.94 mg and 1.88 mg) or benzoyl peroxide (20 mg and 40 mg). Epidermal enlargment, cellular hypertrophy and inflammation were more pronnounced with croton oil treatment. Proliferative stimulus and imbalance between epidermal proliferation and differentiation could be responsible for the hyperplasia, which was more intense with croton oil treatment. The initial proliferative stimulus was reduced after repeated topical treatment with croton oll (1.41 mg) or benzoyl peroxide (30 mg). Croton oll also induced intense hyperkeratosis and regression of initial hyperplasia, which could be related to imbalance between proliferation and differentiation in favour of cellular loss. Twice or thrice a week treatment with benzoyl peroxide induced discrete progression of initial hyperplasia, which could be related to imbalance between proliferation and differentiation predominating a discrete celiular gain. Both substances determined different inflammatory effect, since there was regression with croton oll and progression with benzoyl peroxide. Divergent hyperplastic and inflammatory responses could be reflecting different mechanisms of action of these two com pounds. When croton oil and benzoyl peroxide were administered after methylcholanthrene (0.2 mg) through biphasic or triphasic carcinogenesis protocois, only benzoyl peroxide showed discrete and transitory promotion - propagation - of papiliomas in adult gerbil skin. Taking into account the regression of the proliferative stimulus registered during repeated treatment with both promoters and the response associated to cellular differentiation - hyperkeratosis - it was concluded that those effects interfered in the selective donal expansion of epidermal celis, mainly with croton oll treatment, and could be related to the biological basis of adult gerbil skin relative resistance to chemical epidermal carcinogenesis.